The principles of modern company law - Gower, L. C. B.; Wedderburn of Charlton, Kenneth William Wedderburn, Baron; Weaver, O.; Park, A. E. W. (London: Stevens & Sons, 1969)
This is a text on company law covering the nature and functions and the legislation governing companies. It is accompanied by an Australian supplement.
lje 25/1/19
Loans
Keywords: Corporation law; Company law